2018
DOI: 10.1080/00224499.2018.1517206
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Victimization and Sex-Related Drinking Motives: How Protective is Emotion Regulation?

Abstract: One in five college women experience sexual victimization (SV) and SV severity is associated with subsequent psychological distress including sex-related distress. SV severity may also be associated with drinking motives to cope with sex-related distress and to enhance sex (sex-related drinking motives; SRDM), particularly if individuals suffer from emotion regulation (ER) difficulties. College women (N = 151) completed a survey assessment of ER, SV history, childhood sexual abuse, and SRDM. Twelve regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
1
8
0
1
Order By: Relevance
“…Such results corroborate previous research indicating that individuals who have difficulty controlling their emotions when experiencing negative emotions are more likely to engage in maladaptive strategies to reduce their negative emotional experience, such as drinking or having sex (Bird et al, 2019; Messman-Moore & Ward, 2014; Watkins et al, 2015). Unsurprisingly, individuals who use sex to cope with negative emotions are also more likely to engage in sexual risk behaviors, such as having more sexual partners, than individuals who do not use sex to cope with negative emotions (Gardner, 2017; Grossbard et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Such results corroborate previous research indicating that individuals who have difficulty controlling their emotions when experiencing negative emotions are more likely to engage in maladaptive strategies to reduce their negative emotional experience, such as drinking or having sex (Bird et al, 2019; Messman-Moore & Ward, 2014; Watkins et al, 2015). Unsurprisingly, individuals who use sex to cope with negative emotions are also more likely to engage in sexual risk behaviors, such as having more sexual partners, than individuals who do not use sex to cope with negative emotions (Gardner, 2017; Grossbard et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…However, most research examining the relationship between impulse control difficulties and more general sexual assault victimization has looked at how impulse control difficulties relate to other distal predictors of victimization, such as avoidant coping behaviors, which include drinking or having sex to cope with negative emotions. These results suggest that those who have more difficulty with controlling their impulses are also more likely to drink or have sex to cope (Bird et al, 2019; Messman-Moore & Ward, 2014). Such results are strengthened by a longitudinal study which demonstrated that difficulties with impulse control preceded coping behaviors, in that women’s impulse control difficulties prospectively predicted their subsequent likelihood of drinking to cope (Watkins et al, 2015).…”
Section: Risk Factors For Sexual Assault Victimizationmentioning
confidence: 94%
“…This link may reflect survivors' attempt to overcome post-assault disruptions in social functioning (Resick et al, 1981) by using alcohol as a "social lubricant" (Monahan & Lannutti, 2000). Similarly, some survivors may experience anxiety in sexual situations after an assault and may be motivated to drink to reduce anxiety around sex (Bird et al, 2019). Beyond prepartying to navigate social situations, IR survivors also reported greater motivation to preparty out of concern about barriers to consumption at a main social event, even after controlling for age.…”
Section: Discussionmentioning
confidence: 99%
“…The self-medication hypothesis (Khantzian, 2003) asserts that alcohol is consumed to provide short-term reductions in distress—relief that may be particularly appealing for individuals who otherwise have difficulty regulating distress. In this way, emotion regulation difficulties could lead to increased motivation to drink to cope with distress (Bird et al, 2019) and increased alcohol use for women with SA histories (Lindgren et al, 2012). Additionally, women with SA histories who have less perceived engagement in adaptive coping strategies drink more in response to day-to-day increases in SA-related distress compared to women with greater perceived engagement (Stappenbeck et al, 2015).…”
Section: Associations Among Sa Emotion Regulation and Heavy Drinkingmentioning
confidence: 99%